#AASW6 - fundamental event to launch new research opportunities. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Mellissa Wood, Australian International Food Security Center says that #AASW6 is a huge fundamental event to launch new research opportunities. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/